Evaluation of the clinical significance of serum pentraxin-3 levels in patients with polycystic ovary syndrome - Fatih Yeşil; Köksal Deveci; Pervin Karli (IMR Press, 2022)
Background: Polycystic ovary syndrome (PCOS) is commonly associated with insulin resistance (IR), hyperinsulinemia, and dyslipidemia, which play a role in the development of endothelial dysfunction and promote the early onset of cardiovascular diseases. The aim of this study was to evaluate the clinical importance of pentraxin-3 levels in PCOS patients. Methods: Forty-five female patients diagnosed with PCOS according to the 2003 Rotterdam criteria and 42 healthy women were included in the study. All women studied were tested within 3 and 5 days of their menstrual cycle. Ultrasonographic evaluation of each patient was first conducted using the suprapubic method. Serum PTX-3, endothelin 1 (ET-1), vascular cell adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1), and nitric oxide levels were measured using the enzyme-linked immunosorbent assay method. Results: Pentraxine-3 (PTX-3) levels in the patient group were significantly lower than those in the control group (p < 0.05). PTX-3 levels in the group with hirsutism were significantly higher than those in the nonhirsutism group (p < 0.05). Homeostatic model assessment for IR (HOMA-IR) levels in the patient group were significantly higher than those in the control group (p < 0.01). A weak negative correlation was found between PTX-3 and HbA1c levels. The accuracy rate of the PTX-3 test in distinguishing patients and nonpatients was moderate with a 0.634 area-under-the-curve value. Conclusions: During the follow-up of patients with PCOS, a decrease in serum PTX-3 levels associated with hirsutism and IR may be observed.